Analysis Cluster Scholarship Recipient Student Using K-meansand SAW Methods - Adisimakrisna Peling, Ida Bagus; Agus Ariawan, Made Pasek; Brahupadhya Subiksa, Gede (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Frequently, the determination of scholarship admission cannot be made with confidence, and the established criteria nevertheless need to be taken into account. The scholarship program's goal is to give students who have academic potential but are struggling financially the chance to finish their education without being burdened by hefty expenditures. However, managing and administering scholarships can be a challenging endeavor for educational institutions. In this situation, using a decision support system can improve the efficacy and efficiency of the process of selecting students for scholarships. The results of this research obtained, cluster 1 got rank 1 with the data characteristics of cluster members based on GPA and high value attendance attendance and medium value UKT data, cluster 2 got rank 2 with the data characteristics of cluster member data based on GPA, UKT and high value attendance attendance and cluster 3 got rank 3 with cluster member data characteristics based on GPA, UKT and attendance which had inconsistent values. This study was able to produce priority rankings for each cluster of scholarship recipients based on important factors, like GPA scores, attendance, and UKT, utilizing the SAW and K-meansmethodologies.